Skema Penjaminan Kredit UMKM : Studi Kasus Penanganan Debitur Bermasalah Oleh PT. Jamkrida Jatim - Nataneyla Nasywa K; Leonard Andrie Manafe (JOURNAL OF ECONOMICS, BUSINESS, MANAGEMENT, ACCOUNTING AND SOCIAL SCIENCES, 2025)
Credit guarantee is a strategic instrument to expand access to financing for Micro, Small, and Medium Enterprises (MSMEs) that lack sufficient collateral. PT. Jamkrida Jawa Timur, as a regional credit guarantee institution, plays a crucial role in bridging the risk between MSMEs and financial institutions. This study aims to analyze the credit guarantee scheme implemented by PT. Jamkrida Jatim and evaluate its strategy in handling problematic debtors in 2025. A qualitative approach was employed using a case study method on 40 MSME debtors from different sectors.. The study found that the credit guarantee scheme involved feasibility analysis, risk selection, and regular post-credit monitoring. In handling problematic debtors, PT. Jamkrida Jatim applied strategies such as credit restructuring, mediation with financing institutions, and business assistance. The findings highlight the importance of flexible approaches tailored to the characteristics and responsiveness of each business sector. This study contributes to strengthening a risk-mitigation-based guarantee system that is more adaptive to the dynamics of regional MSMEs..